Multivariate data analysis assisted mining of nutri-rich genotypes from North Eastern Himalayan germplasm collection of Perilla (Perilla frutescens L.) - Kaur, Simardeep; Godara, Samarth; Singh, Naseeb; Kumar, Amit; Pandey, Renu; Adhikari, Sneha; Jaiswal, Sandeep; Singh, Sanjeev Kumar; Rana, Jai Chand; Bhardwaj, Rakesh; Singh, Binay Kumar; Riar, Amritbir (Springer Science+Business Media, 2024)
Understanding the nutritional diversity in Perilla (Perilla frutescens L.) is essential for selecting and developing superior varieties with enhanced nutritional profiles in the North Eastern Himalayan (NEH) region of India. In this study, we assessed the nutritional composition of 45 diverse perilla germplasm collected from five NEH states using standard protocols and advanced analytical techniques. Significant variability was observed in moisture (0.39–11.67%), ash (2.59–7.13%), oil (28.65–74.20%), protein (11.05–23.15%), total soluble sugars (0.34–3.67%), starch (0.01–0.55%), phenols (0.03–0.87%), ferric reducing antioxidant power (0.45–1.36%), palmitic acid (7.06–10.75%), stearic acid (1.96–2.29%), oleic acid (8.11–13.31%), linoleic acid (15.18–22.74%), and linolenic acid (55.47–67.07%). Similarly, significant variability in mineral content (ppm) was also observed for aluminium, calcium, cobalt, chromium, copper, iron, potassium, magnesium, manganese, molybdenum, sodium, nickel, phosphorus, and zinc. Multivariate analyses, including hierarchical clustering analysis (HCA) and principal component analysis (PCA), revealed the enriched nutritional diversity within the germplasm. Correlation analysis indicated significant positive and negative relationships between nutritional parameters, indicating potential biochemical and metabolic interactions present in the perilla seeds. TOPSIS-based ranking identified promising genotypes for functional foods, pharmaceuticals, and nutritional applications. This study provides a first in-depth report of the nutritional composition and diversity of perilla germplasm in the NEH region, thus aiding in the identification of superior varieties for food and nutritional diversification and security.